METHODS FOR MONITORING GRAVITATIONAL FLOW IN SILOS USING TOMOGRAPHY IMAGE PROCESSING - Grudzień, Krzysztof; Sankowski, Dominik (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The article presents the methods of monitoring of the process of gravitational silo discharging with aid of tomography techniques. The described methods apply to funnel and mass flow measurement. The core unit of the presented monitoring system is an image-processing module, while the images are obtained with aid of the electrical capacitance tomography. For the funnel type of flow, the outputs of image processing are parameters describing the process flow, location and material concentration in funnel area. In the case of the mass flow regime the presented method provides information about the parameters of shear zones arising by the wall region of the silo that influence the interaction between the bulk and silo construction during silo discharging.